Revitalisasi Jakaba (Jamur Keberuntungan Abadi) pada Tanaman Bawang Merah sebagai Peningkatan Green Economy - Puspitasari, Yulia Dewi; Cahyanti, Triana Wuri; Nugroho, Purwo Adi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
By providing instruction on shallot processing, this PKM hopes to raise the selling price of shallots. The strategies that are employed are monitoring, planning, and execution. This activity culminates in training on processed shallots. Together, collaborators and resource persons use the supplied tools and materials to manufacture processed shallots. 76 percent of partners now understand and intend to try manufacturing processed shallots because of this engagement. Resource people supply information about packaging, including ordering, pricing, choosing, labeling, and figuring out profit and loss, through partner packaging training. Sixty-eight percent of partners know what packaging is. Online marketing training: Resource people provided partners with information about using the Shopee marketplace for online marketing and setting up accounts for online sales.